Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

I have one question please...I solved it in this way..so I am not sure..that is it right or not? and If I solved it in the wrong way..so would like to know about the correct way and method to solve it..so please :

Solve the equation (x-3) (x+9) (x+5) (x-7) = 385

and here is I solved it in this way :

Solve the equation:
(x-3) (x+9) (x+5) (x-7) = 385
x ( (1-3) (1+9) (1+5) (1-7)) = 385
x ( (-2) (10) (6) (-6) ) = 385
x ( (-20) (6) (-6) ) = 385
x ( (-120) (-6) ) = 385
x ( 720 ) = 385
720x = 385
x = 385/720
x = 0.5347222

waiting for your replies...

share|improve this question
    
Good work on attempting a solution. You can learn a lot from experimenting. With regards to your attempt, when you take x out as a common factor, you have to take x out of all components. So (x-3) = x(1 - 3/x) A good way to test your steps is to expand it out again! –  Fuzz Mar 24 at 14:04
    
@Fuzz Thanks..for encouragment..I quitely do it often..whenever I don't understand..still I solve some way..but not sure..that what I did is in the right way or in the wrong way? –  Umair Shah Mar 24 at 14:11

3 Answers 3

up vote 1 down vote accepted

Some easy ideas to attack your problem with integer solutions:

$$(x-3)(x+9)(x+5)(x-7)=385=5\cdot7\cdot11\implies$$

one of the factors in the LHS must be $\;\pm1\;$ , and after a little action we can see this happens for $\;x=2\;$ since the signs fit nicely (two positive, two negative):

$$(2-3)(2+9)(2+5)(2-7)=(-1)\cdot11\cdot7\cdot(-5)=385$$

Try now also $\;x=-4\;$ ...

share|improve this answer
    
Great...very nice..and very easy way..to solve it..Thanks..I like it...And very easy method to solve the question... –  Umair Shah Mar 24 at 13:25

Let $y = x + 1$ (I got this by taking the average of the four). Then the problem becomes:

$$(y-4)(y+8)(y+4)(y-8) = 385$$

which can be simplified nicely (by multiplying out similar terms) into:

$$\begin{align}(y^2 - 16)(y^2 - 64) &= 385 \\&= 7\cdot55\\&=-7\cdot-55\end{align}$$

The difference between $7$ and $55$ is $48$. But this is exactly the difference between $y^2 - 16$ and $y^2 - 64$. Hence we equate either one (I used $y^2 - 16 = 55$) to deduce that:

$$\begin{align}&y^2 - 16 = 55 \\\implies&y^2 = 71\\\implies &(x+1)^2 = 71 \\ \implies &x = -1\pm\sqrt{71}\end{align}$$

Now, we deal with $-7$ and $-55$ in a similar manner. Equate either one (I used $y^2 - 16 = -7$) to get:

$$\begin{align}&y^2 - 16 = -7 \\\implies&y^2 = 9\\\implies &(x+1)^2 = 9 \\ \implies &x = -1\pm3\end{align}$$

We conclude with with our four solutions for $x$:

$$x = -1\pm\sqrt{71}, -1\pm3$$

The best part: No quadratic formula used!

share|improve this answer
    
Thanks...for your solution..but seriously not getting this way if you can simplify more please..to make it easier for me in understanding.. –  Umair Shah Mar 24 at 13:21
1  
Which part is confusing you? I just made some edits . –  Yiyuan Lee Mar 24 at 13:22
    
Great...Thanks...for solving it to me... –  Umair Shah Mar 24 at 13:29
    
Glad I could help. Since, you are new (i presume) to Math.SE: Do remember to mark any answer posted to your questions if you find it useful and sufficient, via the tick beside it. –  Yiyuan Lee Mar 24 at 13:30
1  
Neat! You might like my explanation of how I came to discover something like this at my sci.math posts Some turbo-charged high school algebra 21 August 2008 and 25 August 2008 (which I've since learned is a somewhat standard technique). –  Dave L. Renfro Mar 24 at 13:52

Observe that $\displaystyle -3+5=-7+9$

So, $$(x-3)(x+5)=x^2+2x-15, (x+9)(x-7)=x^2+2x-63$$

Set $\displaystyle x^2+2x=u$ to find $\displaystyle (u-15)(u-63)=385$

$\displaystyle\implies u^2-78u+560=0$

Using Quadratic Equations Formula, $\displaystyle u=8,60$

or using Middle Term Factor, $\displaystyle u^2-78u+560=u^2-(70+8)u+70\cdot8=(u-70)(u-8)$

So, we have $\displaystyle x^2+2x=8$ or $\displaystyle x^2+2x=70$

Can you take it from here?

share|improve this answer
    
Thanks...for your solution..but seriously not getting this way if you can simplify more please..to make it easier for me in understanding. –  Umair Shah Mar 24 at 13:22
    
@UmairShah, please find the edited version? –  lab bhattacharjee Mar 24 at 13:25
    
Sure...thanks...really...getting this way...now please if you solve it to the end...so will be very kind of you..please –  Umair Shah Mar 24 at 13:27
1  
@UmairShah, If you have understood the solution for $u,$ you should be able to find $x$ in each case –  lab bhattacharjee Mar 24 at 13:29
    
Thanks for your answer....you have solved in a quite good way..but rather as it is in short questions so I will take the easy way to solve it...and this way seems little longer..so I hope that you may not mind....please –  Umair Shah Mar 24 at 14:14

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.